2020
DOI: 10.7150/jca.41316
|View full text |Cite
|
Sign up to set email alerts
|

The role of YWHAZ in cancer: A maze of opportunities and challenges

Abstract: YWHAZ (also named 14-3-3ζ) is a central hub protein for many signal transduction pathways and plays a significant role in tumor progression. Accumulating evidences have demonstrated that YWHAZ is frequently up-regulated in multiple types of cancers and acts as an oncogene in a wide range of cell activities including cell growth, cell cycle, apoptosis, migration, and invasion. Moreover, YWHAZ was reported to be regulated by microRNAs (miRNAs) or long non-coding RNAs and exerted its malignant functions by target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 84 publications
(183 reference statements)
1
73
0
Order By: Relevance
“…Among these genes, YWHAZ (14-3-3ζ) is a member of the 14-3-3 proteins and has multiple functions in various signal transduction pathways [ 39 ]. The overexpression of YWHAZ has been reported in a wide range of cancers, and its aberrant expression contributes to cancer progression and drug resistance [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these genes, YWHAZ (14-3-3ζ) is a member of the 14-3-3 proteins and has multiple functions in various signal transduction pathways [ 39 ]. The overexpression of YWHAZ has been reported in a wide range of cancers, and its aberrant expression contributes to cancer progression and drug resistance [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, YWHAZ (14-3-3ζ) is a member of the 14-3-3 proteins and has multiple functions in various signal transduction pathways [ 39 ]. The overexpression of YWHAZ has been reported in a wide range of cancers, and its aberrant expression contributes to cancer progression and drug resistance [ 39 ]. In PDAC cells, tumor-associated macrophages invade cancer tissues after anticancer drug treatment, and the tumor-associated macrophage-secreted YWHAZ is shown to contribute to chemotherapy resistance [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…14-3-3zeta (also named YWHAZ) is a central hub protein for many signal transduction pathways [157]. Accumulating evidence demonstrates that it acts as an oncogene by targeting downstream protein kinases, apoptosis-associated proteins, and metastasis-related proteins in a wide range of cell activities including cell growth, cell cycle, apoptosis, migration, and invasion.…”
Section: The Interaction Of Tau With Proteins Linked To Cancermentioning
confidence: 99%
“…Accumulating evidence demonstrates that it acts as an oncogene by targeting downstream protein kinases, apoptosis-associated proteins, and metastasis-related proteins in a wide range of cell activities including cell growth, cell cycle, apoptosis, migration, and invasion. It is frequently up-regulated in cancer cells possibly requiring regulation by microRNAs or long noncoding RNAs [157]. Additionally, 14-3-3zeta has shown value as a biomarker for cancer diagnosis, prognosis and chemoresistance [157].…”
Section: The Interaction Of Tau With Proteins Linked To Cancermentioning
confidence: 99%
“…Tyrosine 3 monooxygenase/tryptophan 5-monooxygenase activation protein zeta, also named YWHAZ or 14-3-3ζ, is a key modulator on the β-catenin signaling pathway and is closely associated with tumorigenesis and cancer metastasis (13). YWHAZ has been shown to be overexpressed in multiple types of cancers and regulated by miRNAs or lncRNAs (14). Zeng Y et al reported that lncRNA LUCAT1/miR-134-5p/YWHAZ axis can promote proliferation and invasion of GC (15); Wang H et al found circ-SERPINE2/miR-375/YWHAZ axis promote proliferation (16) and Jin CX et al clari ed how YWHAZ effects apoptosis and autophagy in GC (17).…”
Section: Introductionmentioning
confidence: 99%